IMPROVING READING COMPREHENSION OF ELEVENTH-GRADE STUDENTS THROUGH TPS TECHNIQUE - Fadjar; Kamaruddin , Abdul; Anggreni, Afrillia (Tadulako University, 2023)
This research aims at finding out whether or not the implementation of Think- Pair-Share (TPS) Technique can improve the reading comprehension of the eleventh-grade students of SMA Negeri 1 Banawa. This research employed a quasi-experimental research design which involved two groups of students as experimental and control groups. The samples were selected by using a purposive sampling technique. The samples were the students of XI IPS 2 as the experimental group and XI IPS1 as the control group. The instrument of this research was a test that was given to the sample as a pretest and posttest in the form of a reading test. The result of data analysis shows that the mean score of the posttest in the experimental group is 76.82 which is considered higher than the mean score of posttest in control group (65.06). By applying 42 degrees of freedom (df) and 0.05 level of significance, it indicates that the tconted (3.84) is higher than the ttable (2.01). As a result, it clarifies that the hypothesis of this research is accepted. In conclusion, the findings of this research reveal that students’ reading comprehension can be effectively improved by using Think-Pair-Share (TPS)